2021
DOI: 10.1371/journal.pone.0247036
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: The Youth and Mental Health Study (YAMHS) – a longitudinal study of the period from adolescence to adulthood

Abstract: The aim of this article is to provide a detailed description of the Youth and Mental Health Study (YAMHS),a population-based, representative (cluster sampling), prospective cohort study that was conducted to investigate risk and resilience factors for mental health conditions, specifically depressive symptoms and disorders, from adolescence to adulthood. The baseline data were collected in 1998 (T1) in two counties in central Norway from 2464 adolescents (response rate 88.3%, mean age 13.7 years). The first fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…Attrition analysis indicated that the responders at T4 were more frequently female than were the non-responders, and fewer responders had a non-Norwegian ethnicity. The upper middle class was overrepresented among the parents of the responders, while workers were underrepresented (40).…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attrition analysis indicated that the responders at T4 were more frequently female than were the non-responders, and fewer responders had a non-Norwegian ethnicity. The upper middle class was overrepresented among the parents of the responders, while workers were underrepresented (40).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…The current study used data from the Youth and Mental Health Study (YAMHS), a population-based, representative (cluster sampling with schools as the units), prospective cohort study that was conducted to investigate risk and resilience factors for mental health conditions, specifically depressive symptoms and disorders, from adolescence to adulthood (40). The first data were collected in 1998 (T1) in two counties in central Norway from 2,464 adolescents (response rate 88.3%, mean age 13.7 years, 50.8% female).…”
Section: Study Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence is a key-developmental stage not only for physical, neurological, but also for psychological and social changes. In this developmental stage, a large number of people struggle with mental health problems like stress, anxiety, or depression [ 9 – 11 ]. Although young people from socioeconomic disadvantaged families or neighbourhoods are at increased risk of being stressed [ 12 , 13 ], socioeconomic differences only explain a minor part of the increase in stress among young people in Denmark [ 14 ] and internationally [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this developmental stage, a large number of people struggle with mental health problems like stress, anxiety, or depression [ 9 – 11 ]. Although young people from socioeconomic disadvantaged families or neighbourhoods are at increased risk of being stressed [ 12 , 13 ], socioeconomic differences only explain a minor part of the increase in stress among young people in Denmark [ 14 ] and internationally [ 9 – 11 ]. Stress in young people is increasingly understood as a negative consequence of wider social trends in the “Performance Society” [ 15 , 16 ], in which control over and success in life have become dominant ideals [ 17 ].…”
Section: Introductionmentioning
confidence: 99%